The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.5935/0103-507x.20220102-en
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of peripheral ischemic microvascular reserve in sepsis is not related to calcitonin gene-related peptide or substance P

Abstract: Objective To evaluate the mechanisms attributed to the prognostic value of peripheral ischemic microvascular reserve in patients with sepsis. Methods This observational cohort study enrolled 46 consecutive septic patients in the intensive care unit between November 2020 and October 2021. After fluid resuscitation, the peripheral ischemic microvascular reserve was evaluated using the association of postocclusion reactive hyperemia with the peripheral perfusion index. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…to play an essential role in the peak/timing of hyperemia [23,24]. Additionally, the neuropeptide substance P and calcitonin gene-related peptide are known markers of severity in sepsis [25][26][27], although we recently demonstrated no significant correlations between these neuropeptides and PIMR in septic patients [28]. One also must remember that sepsis exhibits an essential inflammatory response [29].…”
Section: Plos Onementioning
confidence: 90%
See 2 more Smart Citations
“…to play an essential role in the peak/timing of hyperemia [23,24]. Additionally, the neuropeptide substance P and calcitonin gene-related peptide are known markers of severity in sepsis [25][26][27], although we recently demonstrated no significant correlations between these neuropeptides and PIMR in septic patients [28]. One also must remember that sepsis exhibits an essential inflammatory response [29].…”
Section: Plos Onementioning
confidence: 90%
“…Although the pathophysiological mechanisms of PORH in the skin are not fully understood, a report showed that the expression and release of neuropeptides via sensory nerves and derivatives from cytochrome P-450 epoxygenases seem to play an essential role in the peak/timing of hyperemia [ 23 , 24 ]. Additionally, the neuropeptide substance P and calcitonin gene-related peptide are known markers of severity in sepsis [ 25 27 ], although we recently demonstrated no significant correlations between these neuropeptides and PIMR in septic patients [ 28 ]. One also must remember that sepsis exhibits an essential inflammatory response [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation